Hyporesponsiveness to intradermal administration of hepatitis B vaccine in insulin dependent diabetes mellitus. Issue 1 (1st January 1998) - Volti, S Li; Caruso-Nicoletti, M; Biazzo, F; Sciacca, A; Mandarà, G; Mancuso, M; Mollica, F
Abstract : The immune response to intradermal or intramuscular hepatitis B vaccine in 18 children with insulin dependent diabetes mellitus (IDDM) compared with 24 healthy children was studied. Patients were divided into responders, hyporesponders, and non-responders according to their antihepatitis B serum concentrations after hepatitis B vaccination. We also studied HLA class II antigen distribution and did delayed type hypersensitivity (DTH) tests on children with IDDM and controls.  No difference in the immune response (antihepatitis B surface antigen antibody titres) was found with intramuscular administration, whereas with intradermal administration a statistically lower immune response (p < 0.001) was observed in children with IDDM v controls. This hyporesponsiveness cannot be attributed to HLA class II antigen distribution because their frequency was the same in both groups of children with IDDM.  It is suggested that the poor immune response to intradermal hepatitis B vaccine may be due to impaired macrophage activity resulting in failure of antigen presentation, which may be of importance in the immune dysfunction in children with IDDM. This hypothesis is suggested by a significantly lower score on a DTH test to a battery of antigens in the IDDM group when compared with controls. It is therefore suggested that when the hepatitis B vaccination is offered to children with IDDM it may be preferable to give it intramuscularly.